(untitled) (Journal of Pakistan Orthopaedic Association, 2018)
Objectives: To find out the prevalence of lumbosacral transitional vertebrae (LSTV) among patients presented to Hayatabad medical complex, Peshawar. Methods: This prospective observational study was conducted at Hayatabad Medical Complex Peshawar by Department of Orthopaedic & Spine Surgery. Study duration was one and half year from Jan 2015 to Jun 2016. In this prospective study, all those patients were included in whom lumbosacral spine x-rays were done regardless of the pathology. LSTV was identified and classified according to Castellvi classification. Results: In a total of 4939 patients, x-rays were examined with 574(11.6%) having LSTV. Mean age of the group with LSTV was 32.89 years + 10.12SD with minimum of 13 and maximum of 64 years. The overall prevalence of lumbarization was 2.1% and of Sacralization was 9.55%. According to Castellvi classification, distribution of various types of LSTV in the group was: type I (22.6%), type II (44.9%), type III (25.1%) and type IV (7.3%). Conclusion: LSTV is very common condition with prevalence of 11.6 % in our study and reported as high as 30% in other studies. It should be take into account while doing spine surgery